Testing Marx: Capital Accumulation, Income Inequality, and Socialism in Late Nineteenth-Century Germany - Bartels, Charlotte; Kersting, Felix; Wolf, Nikolaus (The Review of Economics and Statistics, 2025)
Abstract We study the dynamics of capital accumulation, income inequality, capital concentration, and voting up to 1914. Based on new panel data for Prussian regions, we reevaluate the famous revisionism debate between orthodox Marxists and their critics. We show that changes in capital accumulation led to a rise in the capital share and income inequality, as predicted by orthodox Marxists. But against their predictions, this neither led to further capital concentration nor more votes for the socialists. Instead, trade unions and strike activity limited income inequality and fostered political support for socialism, as argued by the revisionists.